Rise of the Composite Present Perfect Tense in Polish with the Verb mieć 'to Have' as an Auxiliary - Kida, Ireneusz (Slavia Centralis, 2020)
In this paper we discuss the phenomenon of the rise of the complex present perfect tense in modern Polish in the context of three IndoEuropean languages: English, German, and Spanish. Although the category of the present perfect tense does not exist in grammar books of the Polish language, it will probably soon need to be included, and the present perfect tense will be treated as a separate grammatical tense, as is the case in English and Spanish. While discussing the trajectory of the development of the present perfect tense in Englishand Spanish, we arrive at the conclusion that the Polish language is undergoing a similar process.
Keywords: present perfect tense; grammaticalisation; possession; verb 'to have'; Polish